2021
DOI: 10.1088/1755-1315/712/1/012039
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rhizophora sp mangrove leaf extract on mice blood glucose levels

Abstract: Diabetes mellitus is a disease that occurs due to increased blood glucose levels (hyperglycemia) due to disorders of the pancreas. Mangrove leaves are known as herbal plants that can reduce blood glucose levels because it contains flavonoid compounds that can repair damaged pancreatic β cells and stimulate pancreatic β cells to produce the hormone insulin. This study aimed to determine the effect of Rhizophora leaf extract administration in reducing blood glucose levels of mice. This research was an experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
0
0
Order By: Relevance
“…Moreover, Efendi et al reported that the administration of Rhizophora leaf extract in the treatment group was able to reduce blood glucose levels in comparison to before treatment. With a dosage of 500 mg/kg BW, there was a 29% decrease in fasting blood sugar levels [50]. These findings confirmed that R. stylosa possessed an anti-diabetic profile.…”
Section: Anti-diabetic Propertysupporting
confidence: 70%
“…Moreover, Efendi et al reported that the administration of Rhizophora leaf extract in the treatment group was able to reduce blood glucose levels in comparison to before treatment. With a dosage of 500 mg/kg BW, there was a 29% decrease in fasting blood sugar levels [50]. These findings confirmed that R. stylosa possessed an anti-diabetic profile.…”
Section: Anti-diabetic Propertysupporting
confidence: 70%